2018
DOI: 10.1038/nrgastro.2017.169
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs in hepatocellular carcinoma: molecular functions and pathological implications

Abstract: Hepatocellular carcinoma (HCC) is a leading lethal malignancy worldwide. However, the molecular mechanisms underlying liver carcinogenesis remain poorly understood. Over the past two decades, overwhelming evidence has demonstrated the regulatory roles of different classes of non-coding RNAs (ncRNAs) in liver carcinogenesis related to a number of aetiologies, including HBV, HCV and NAFLD. Among the ncRNAs, microRNAs, which belong to a distinct class of small ncRNAs, have been proven to play a crucial role in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
301
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(321 citation statements)
references
References 196 publications
3
301
0
Order By: Relevance
“…LncRNAs have been established as crucial regulators in pathogenesis, especially in malignancies [32]. In the present study, we used TCGA data to determine a landscape of differentially expressed lncRNAs in HCC, which revealed a significant upregulation of LINC00958 in HCC.…”
Section: Discussionmentioning
confidence: 95%
“…LncRNAs have been established as crucial regulators in pathogenesis, especially in malignancies [32]. In the present study, we used TCGA data to determine a landscape of differentially expressed lncRNAs in HCC, which revealed a significant upregulation of LINC00958 in HCC.…”
Section: Discussionmentioning
confidence: 95%
“…Third, RNA-Seq has a better accuracy and repeatability [9][10][11][12]. Advances in RNA-Seq have enabled the examination of HCC at high resolution [13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a subset of conserved, single-strand, small non-coding RNAs (18-24nt), which can regulate gene expression by base-pairing to the 3′-UTR of the target mRNA and subsequently changing mRNA degradation and/or translational dysfunction. 4,5 Accumulating studies have found that miRNAs are aberrantly expressed and dysfunctional in HCC. [6][7][8][9] Recently, miR-NAs have been shown to be associated with diagnosis, development, progression and prognosis of human HCC.…”
Section: Introductionmentioning
confidence: 99%